Role of edaphic arthropods on the biological control of the olive fruit fly (Bactrocera oleae) - Dinis, Ana Maria (2015)
The olive fruit fly, Bactrocera oleae (Rossi) is a major pest of the olive tree. A great part of its life cycle is spent inside the olive fruit, which hinders the action of natural enemies. However, pupation usually occurs on the ground, which makes this stage more vulnerable to predation by edaphic arthropods. In this context, with the present work, it was studied the role of the edaphic arthropods on the biological control of olive fruit fly. Under laboratory conditions, Calathus granatensis Vuillefroy and Pterostichus globosus Quensel, two species of carabids abundant in groves of Trás-os-Montes were evaluated as potential predators of olive fruit fly. The food preferences of both carabids were studied as olive fruit fly pupae were offered together with pupae of the Mediterranean fruit fly (Ceratitis capitata Wiedemann) in different proportions. It was also evaluated the functional responses of both carabids on different densities of olive fruit fly pupae. Under field conditions predation by edaphic arthropods on olive fruit fly pupae was evaluated using exposed-exclusion boxes to predators along with pitfall traps for capture of the arthropods active near the boxes. The assay was conducted in two olive groves of the region of Mirandela (northeast of Portugal) between January and May. Biological control provided by edaphic arthropods was measured by calculating biological control services indexes that were further correlated with the abundance of arthropods and functional groups captured in the pitfall traps. The results of the laboratory experiments indicate that both species of carabids studied preyed olive fruit fly pupae, however, C. granatensis proved to have more preference for olive fruit fly pupae over the alternative prey independently of the offered ratio whereas P. globosus demonstrated no preference for olive fruit fly having consuming the two types of pupae. This species of carabid proved to be more polyphagous and revealed a "switching" behavior. The functional response curves demonstrated that both carabids exhibited a type II functional response in which the number of pupae consumed increased as the density of offered pupae increased until it reached a plateau where the consumption remained constant regardless of the offered density. In the field experiment, it was demonstrated that family Formicidae, the order Araneae and family Forficulidae dominated the arthropod community, wherein family Formicidae dominated during the period between the end of winter and beginning of spring and Forficulidae during the winter period. Concerning functional groups, omnivorous arthropods dominated the community, followed by granivorous and predators. The maximum value of biological control services index was achieved in the period between late winter and early spring, when the abundance of predators and omnivorous arthropods reached its maximum. Relationships between the presence of these two functional groups and the biological service index values were found, especially the presence of omnivorous, in which the family Forficulidae stood out during the winter period and family Formicidae during the spring period. The results demonstrate that important biological control services can be provided by edaphic arthropods against olive fruit fly pupae in olive groves. These services are the result of great complementarity among arthropods groups in the different periods of the year. On one hand, during the fall, groups of arthropods such as carabids can be important predators of olive fruit fly pupae and during the period of winter and beginning of spring, omnivorous arthropods such as insects from families Forficulidae and Formicidae may have higher importance. Therefore, it becomes necessary to conserve these groups of arthropods in olive groves in order to maintain or even increase the biological control services against the olive fruit fly.